IMPLEMENTASI PEMBERIAN REWARD DAN PUNISHMENT UNTUK MENINGKATKAN ETOS KERJA GURU - Denny Bhekti Kurnianto; Siti Aimah (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This study aims to describe the implementation of reward and punishment in improving the work ethic of teachers in the school environment. The approach used is a qualitative approach with a case study research type. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. Data validity checks are carried out using source and technique triangulation techniques. The results of the study indicate that giving rewards such as awards, bonuses, and formal recognition can increase teacher motivation and work enthusiasm. Meanwhile, punishments that are carried out fairly and educatively, such as reprimands and coaching, can increase discipline without reducing work enthusiasm. The contribution of this study provides strategic understanding for school management in building a productive work culture through a balanced reward and sanction system